Budgeting and employee stress in times of crisis: Evidence from the Covid-19 pandemic - Bedford, David S.; Speklé, Roland F.; Widener, Sally K. (Accounting, Organizations and Society, 2022)
Prior research has shown that that management control practices change in response to global crises, yet we have little understanding of the behavioral consequences of these changes. The purpose of this study is to explore the behavioral effects that stem from crisis-induced changes to management control practices and the factors that intensify or diminish these effects. Using survey data from business unit managers in the Netherlands, our results show that firms tighten their budget controls in response to a negative impact of Covid-19. In turn, the tightening of budget controls is positively associated with employees' emotional exhaustion because of increased perceptions of role ambiguity and role conflict. We furthermore find that the effect of tighter budget controls on role ambiguity is mitigated when managers perceive that the budget controls are used in an enabling way prior to the crisis but heightened with increased trust in senior management. These results suggest that if firms use their budgets to help managers acquire a deeper understanding of their tasks and responsibilities, they are better able to respond to a negative shock and the accompanying tightening of budget controls, which helps mitigate the undesired behavioral response of increased role ambiguity and emotional exhaustion. Our findings also suggest that trust, which usually is beneficial to organizations, has a ‘dark’ side in that managers will push themselves harder to reciprocate the trust they have in their senior managers, which exacerbates the effect of tighter budget controls on role ambiguity and, in turn, emotional exhaustion.